Pengaruh Promosi dan Merek Terhadap Minat Berkunjung di Terminal Wisata Grafika Cikole - Mulyana, Hadi; Fajri, Khoirul (Manajemen dan Pariwisata, 2024)
The research was conducted at Terminal Wisata Grafika Cikole, located at Jl. Raya Tangkuban Parahu No KM 8, Cikole, Kec. Lembang, Bandung Barat Regency, West Java. The title of the research is "The Influence of Promotion and Brand on Visiting Interest at Terminal Wisata Grafika Cikole" using quantitative methods of multiple linear regression analysis and descriptive and verificative analysis. The independent variables are Promotion and Brand, and the dependent variable is Visiting Interest. The sample size used is 100 respondents. The research objective is to determine the influence of independent variables on the dependent variable. The results of the instrument test indicate that all questionnaire statements are valid and reliable. The descriptive research results show that Promotion, Brand, and Visiting Interest are all categorized as "Good". Verificative analysis results show that the Promotion and Brand variables have a positive and significant influence on Visiting Interest both partially and simultaneously. The coefficient of determination or R2 value is 65.80%, and the remaining (34.20%) is influenced by other variables outside of this study.